The contribution of student’s perception on majors toward student’s career planning - Ahmad Syaf Ya Habibi; Neviyarni Neviyarni; Marjohan Marjohan (Fakultas Ilmu Pendidikan UNP)
Career planning is important in the career development of students. Students in achieving careers often experience obstacles, for it takes an effort to overcome them. Student's perceptions on Majors are the factor that allegedly affects student's career planning. This study aims to describe the contribution of student's perceptions on majors toward student’s career planning. This research used a quantitative approach with a correlational descriptive method. The population was 380 and the sample was 195 students. The instrument about student’s perception on majors and student's career planning used Likert scale model with reliability 0.957. Data were analyzed using simple regression technique. The result shows that student's perception on majors was positive and student’s career planning in the high category. There is a contribution (33.6%) of student's perception on majors towards student’s career planning.